Clinicopathological characteristics, evolution, treatment pattern and outcomes of hormone-receptor-positive/HER2-low metastatic breast cancer - You, Shuhui; Gong, Chengcheng; Li, Yi; Xie, Yizhao; Li, Yumeng; Zhao, Yannan; Wang, Biyun (Frontiers in Endocrinology, 2023)
Objective: Despite the promising efficacy of the novel antibody-drug conjugate trastuzumab deruxtecan in treating Hormone Receptor (HoR)-positive/Human Epidermal Growth Factor Receptor 2 (HER2)-low metastatic breast cancer (MBC), its categorization as a distinct entity remains disputed, as does the divergence in its endocrine and chemotherapy outcomes. This study aimed to elucidate the clinical characteristics, primary/metastatic lesion HER2 expression, and treatment outcomes of HoR-positive/HER2-low patients. Methods: We included HoR-positive/HER2-negative MBC patients who underwent 1st and 2nd line endocrine treatment from July 2010 to October 2022 at the Fudan University Shanghai Cancer Center, comparing the clinical pathological characteristics, HER2 expression in primary/metastatic lesions, treatment, and therapeutic effects of the HER2-low and HER2-zero groups. Results: Among the 458 HoR-positive/HER2-negative MBC patients, 54.37% (249/458) were HER2-low. The HER2-low group and the HER2-zero group had similar clinical pathological characteristics and similar progression-free survival (PFS) of 1st and 2nd line endocrine treatment (median PFS: 8.05 months vs 10.12 months, p=0.114, HR 1.257, 95% CI 0.771 to 1.028). The PFS of the HER2-low and HER2-zero groups was also similar, treated with different endocrine drugs (including aromatase inhibitors, tamoxifen/toremifene, fulvestrant, palbociclib, and everolimus). However, the HER2-low group had significantly shorter PFS during 1st and 2nd line chemotherapy compared to the HER2-zero group (median PFS: 8.64 vs 9.03 months, p=0.027, HR 0.841, 95% CI 0.721-0.980). Additionally, 41.18% (63/153) of patients exhibited a change in HER2 expression between primary and metastatic lesions. Notably, patients whose HER2 status changed from zero to low expression had significantly prolonged PFS during chemotherapy compared to those who maintained low HER2 expression (median PFS: 14.29 vs 11.27 months, p=0.048, HR 0.597, 95% CI 0.358-0.996). Conclusion: In HoR-positive MBC, patients with low and zero HER2 expression have similar clinical characteristics and respond similarly to endocrine treatment, but the chemotherapy effect is worse in the HER2-low patients. Moreover, the transformation of HER2 status from primary to metastatic lesions may have potential influence on chemotherapy outcomes. Therefore, the expression and heterogeneity of HER2 should be considered in clinical decisions.